PERBEDAAN PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBANTUAN PETA PIKIRAN DENGAN DIRECT INSTRUCTION TERHADAP HASIL BELAJAR SISWA PADA POKOK BAHASAN PROGRAM LINEAR - Nur Rohman (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
The objectives of this research are to investigate whether there is difference of influence student learning result after application of cooperative script learning model assisted mind map with direct instruction learning model on the subject of Program Linear class X of SMA Plus Al-Amanah Balongsumber Dander Bojonegoro in the academic year of 2014/2015. This study is a quasi-experimental study using a study design of post-test - only control design. The sampling technique using cluster random sampling technique. The sample in this research is class X-B as an experimental class and class X-C  as the control class. Data mathematics learning result obtained using the technique of tests, and the tests used in the form of an objective test. Data were analyzed by an independent comparative statistical t-test. Based on the research results, it was concluded that: there is a significant difference between students' mathematics learning result that learned through the cooperative scriptlearning model assisted mind map with the students that learned through direct instruction learning. This suggests there are differences in the effect of the cooperative script learning model assisted mind map with direct learning model mathematics instruction on learning result of students on the subject of Program Linear second semester of class X SMA Plus Al-Amanah Bojonegoro.